A feasibility study for a randomised controlled trial of the Positive Reappraisal Coping Intervention, a novel supportive technique for recurrent miscarriage. Issue 4 (15th April 2015) - Bailey, Sarah; Bailey, Chris; Boivin, Jacky; Cheong, Ying; Reading, Isabel; Macklon, Nick
Abstract : Introduction: Recurrent miscarriage (RM) is diagnosed when a woman has had three or more miscarriages. Increased levels of distress and anxiety are common during the waiting period of any subsequent pregnancies, posing a significant threat to psychological well-being. However, only limited support and therapy are available for these women, and many are left to cope alone. The Positive Reappraisal Coping Intervention (PRCI) is a novel self-administered supportive technique which has been shown to be effective in patients awaiting the outcome of in vitro fertilisation treatment. The primary objective of this study is to assess the feasibility and effectiveness of the PRCI in improving quality of life in the difficult waiting period which women with previous RM endure before an ongoing pregnancy can be confirmed. Methods and analysis: A randomised controlled trial (RCT) feasibility study will establish the viability of conducting a multicentre RCT to definitively test the effects of the PRCI on the psychological well-being of women who have experienced RM during the initial waiting period of a subsequent pregnancy. A second component consists of a qualitative process evaluation exploring the initial experience of pregnancy following repeated miscarriages. Participants (n=50) will be randomised into one of two groups. The PRCI intervention group will receive the PRCI card and weekly questionnaires to assess their psychological well-being during the waiting period of their new pregnancy. The non-intervention group will be asked to complete the same weekly questionnaires. The qualitative process analysis will employ semistructured interviews (n=20) to address relevant aspects of the study objectives. Ethics and dissemination: Ethics approval has been obtained from the National Research Ethics Service Committee South Central—Hampshire A. Participating centres have given National Health Service R&D approval. Study findings will be disseminated through peer reviewed journals, national and international conferences and lay user groups. Trial registration number: ISRCTN43571276. This study was registered with the ISRCTN 18 /02/2014 following adoption onto the United Kingdom Clinical Research Network (UKCRN) portfolio. Recruitment of the first participant occurred 04/02/2014.